Kid's World Kindergarten / Nur Fatimi Yusof ... [et al.] - Yusof, Nur Fatimi; Mat Rashid, Siti Nafhatun Huwaina; Zurda, Farah Luyiana; Ab. Karim, Siti Maisarah; Md Dosah, Noor Azeyanti (Faculty of Applied Sciences, 2003)
Kid's World Kindergarten is a per-school or kindergarten dedicated to provide knowledge for children from the age of 4 to 6 years old. Kid's World Kindergarten is a kindergarten that provides basic education such as reading, writing and calculating for children. We are very concern with children and will give them the best children. We will also ensure their safety and make sure that they will feel them being loved.